Tissue specific imprinting on innate lymphoid cells during homeostasis and disease process revealed by integrative inference of single-cell transcriptomics - Song, Peng; Cao, Ke; Mao, Yonghuan; Ai, Shichao; Sun, Feng; Hu, Qiongyuan; Liu, Song; Wang, Meng; Lu, Xiaofeng; Guan, Wenxian; Shen, Xiaofei (Frontiers in Immunology, 2023)
Innate lymphoid cells (ILCs) are key components of the immune system, yet the similarity and distinction of the properties across tissues under homeostasis, inflammation and tumor process remain elusive. Here we performed integrative inference of ILCs to reveal their transcriptional profiles and heterogeneity from single-cell genomics. We collected a large number of ILCs from human six different tissues which can represent unique immune niches (circulation, lymphoid tissue, normal and inflamed mucosa, tumor microenvironment), to systematically address the transcriptional imprinting. ILCs are profoundly imprinted by their organ of residence, and tissue-specific distinctions are apparent under pathological conditions. In the hepatocellular carcinoma microenvironment, we identified intermediate c-kit+ ILC2 population, and lin-CD127- NK-like cells that expressed markers of cytotoxicity including CCL5 and IFNG. Additionally, CD127+CD94+ ILC1s were preferentially enriched in inflamed ileum from patients with Crohn’s disease. Together, these analyses depicted a comprehensive characterization of ILC anatomical distribution and subset heterogeneity, and provided a baseline for future temporal or spatial studies focused on tissue-specific ILC-mediated immunity.